2022
DOI: 10.3389/fpsyt.2021.810814
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Introductory Training in Trauma-Informed Care Into Mental Health Rehabilitation Services: A Mixed Methods Evaluation

Abstract: ObjectiveThis paper describes the implementation of training in trauma-informed care (TIC) across a mental health rehabilitation service.MethodA mixed-methods approach was applied incorporating baseline measures of staff attitudes toward TIC, quantitative description of staff training participation, and semi-structured interviews of Team Leaders' views on the implementation of TIC.ResultsFifty-five of 123 staff responded to the Organizational Change Readiness Assessment (OCRA) survey (44.7%). Training completi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It is common for young people seeking mental health treatment to have a history of trauma. It is well known that trauma permeates society and has an impact on how people with mental illnesses develop, behave, and are treated (Nation, 2022). Furthermore, those suffers from mental health issues and those who have experienced trauma disproportionately are impacted by the lack of widespread adoption of person-centered treatment in healthcare settings.…”
Section: Figure 1: Theoretical Framework On Youth Safe Spacementioning
confidence: 99%
“…It is common for young people seeking mental health treatment to have a history of trauma. It is well known that trauma permeates society and has an impact on how people with mental illnesses develop, behave, and are treated (Nation, 2022). Furthermore, those suffers from mental health issues and those who have experienced trauma disproportionately are impacted by the lack of widespread adoption of person-centered treatment in healthcare settings.…”
Section: Figure 1: Theoretical Framework On Youth Safe Spacementioning
confidence: 99%
“…in TIC were associated with a reduced e cacy in TIC. However,Nation et al, (2022) disagree with this assertion and posit that training is unlikely to bring about the shift in behavior needed to ingrain TIC in health care provider's service delivery.…”
mentioning
confidence: 99%
“…More mental health professionals need to experience a personal transformation of their attitudes toward TIC to facilitate the implementation of TIC into clinical practice. 3,13,14 In addition, the review suggested that barriers to routine integration of TIC into health care settings include a lack of available training and unclear best-practice guidelines. 7…”
mentioning
confidence: 99%
“…More mental health professionals need to experience a personal transformation of their attitudes toward TIC to facilitate the implementation of TIC into clinical practice. 3,13,14 In addition, the review suggested that barriers to routine integration of TIC into health care settings include a lack of available training and unclear bestpractice guidelines. 7 A previous study suggested that applying the psychological first aid (PFA) approach among health care professionals may provide a valuable foundation to build a proactive trauma-informed approach to patients at all points of contact across the health care system, including critical care settings.…”
mentioning
confidence: 99%